Covert advertising as inadmissible presentation of information - Tomažič, Tina (Array, 2014)
The purpose of this paper is to identify and redefine the categories of covert advertising, to demonstrate the covert aspects of advertising in the press, to provide a high-quality comparison of three leading Slovenian newspapers and to prepare a model for future researchers.In this article, we defined, analysed, and explored covert advertising. In the first part we used descriptive approach, and method of compilation. In the empirical part we used content analysis to research texts of covert advertising ; we used analytical approach. The results of the research indicate that covert advertising appears on a daily basis in daily newspapers and these articles are visually more attractive to garner greater attention from readers and offer numerous visual presentations.